2009
DOI: 10.1063/1.3182851
|View full text |Cite
|
Sign up to set email alerts
|

Atomic hydrogen adsorption and incipient hydrogenation of the Mg(0001) surface: A density-functional theory study

Abstract: We investigate the atomic hydrogen adsorption on Mg(0001) by using density-functional theory within the generalized gradient approximation and a supercell approach. The coverage dependence of the adsorption structures and energetics is systematically studied for a wide range of coverage Theta [from 0.11 to 2.0 monolayers (ML)] and adsorption sites. In the coverage range 0 < Theta < 1.0, the most stable among all possible adsorption sites is the on-surface fcc site followed by the hcp site, and the binding ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
(47 reference statements)
3
5
0
Order By: Relevance
“…This structure is energetically favorable, and the computed binding energy is -0.20 eV, relative to H . This is consistent with other theoretical studies that have computed favorable binding energies for atomic H absorbed at subsurface sites [54][55][56]. Moreover, it is reasonable for an arrangement like that shown in Fig.…”
Section: Hydrogen Evolution Reaction (Her)supporting
confidence: 92%
“…This structure is energetically favorable, and the computed binding energy is -0.20 eV, relative to H . This is consistent with other theoretical studies that have computed favorable binding energies for atomic H absorbed at subsurface sites [54][55][56]. Moreover, it is reasonable for an arrangement like that shown in Fig.…”
Section: Hydrogen Evolution Reaction (Her)supporting
confidence: 92%
“…The calculated PDOSs are well consistent with other theoretical results. 30,31 High similarity on the PDOSs between the surface and bulk Mg atoms (Mg1 and Mg2) is noted. Both show a main bonding peak at −5.0 eV.…”
Section: Adsorptions Of Hydrogenmentioning
confidence: 94%
“…The H−Mg chemical bonding during surface hydrogenation displays a mixed ionic/ covalent character. 31 The compressive (negative) strain facilitates the formation of the H−Mg−H trilayers due to the fact that the lattice constant of H−Mg−H trilayer is shorter than that of pure Mg. 32 Furthermore, studies on the absorption/desorption of hydrogen on Ti or TiAl are reported . 33,34 Hydrogen atoms prefer to pair up and form clusters in Mg, but they are likely to occupy the sites apart as far as possible in Ti.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some earlier ab initio investigations concerning adsorbates on magnesium have concentrated on the ability of magnesium to break the hydrogen bond and to store atomic hydrogen. [14][15][16][17] This work is organized as follows: In Sec. II we first consider in detail the present state of the art method for producing BNNTs and then explain our strategy for studying boron-nitride chemistry on magnesium.…”
Section: Introductionmentioning
confidence: 99%